The Specific Impacts of Quantum Leadership Principles on Creativity Metrics and Uncertainty Management Strategies in Educational Institutions, A Literature Review - Soni Wandrial (Asian Journal of Management Analytics, 2026)
This systematic review of 40 studies examined the impacts of quantum leadership principles on creativity and uncertainty management in educational institutions across diverse contexts spanning K-12 and higher education settings in 15 countries.  While direct creativity measurement was limited to only 6 studies, available evidence demonstrated positive effects: quantum learning interventions produced higher creative thinking scores (mean 17.00 vs.  13.48 in controls), and quantum leadership principles operated primarily through indirect organizational mechanisms, with organizational trust mediating 46% of variance in creative outcomes (F=206.79, p<.001). Additional outcomes included improved teacher performance with sustained leadership relationships, organizational culture shifts toward collaboration and innovation, and enhanced staff satisfaction under supportive leadership environments.